PENGUKURAN KINERJA NON KEUANGAN TERHADAP KINERJA KARYAWAN: EFEK MEDIASI DARI ROLE CLARITY DAN KOMITMEN - Hidayatul Khusnah; Mardiyah Anugraini (STIE Mahardhika, 2022)
This study aims to examine the mediating effect of role clarity and organizational commitment on the effect of non-financial performance measurement on employee performance. In addition to examining the mediating effect, this study also examines the direct influence of non-financial performance measurements on role clarity, organizational commitment, and employee performance. The sample of this research is 153 financial managers of companies that are members of PT. SIER The data analysis technique in this study uses Partial Least Square with WarpPLS 6.0 software. The results of this study indicate that non-financial performance measurement has a positive effect on employee performance, role clarity and organizational commitment. Further results show that organizational commitment has an effect on employee performance. However, for the effect of role clarity on employee performance, it was found that the results did not support the hypothesis, namely, that role clarity had no effect on employee performance. The results of testing the mediation hypothesis found that role clarity was able to fully mediate the effect of non-financial performance measurements on employee performance. While the organizational committee is also able to partially mediate the effect of non-financial performance measurement on employee performance.